Comparative transcriptome analysis of the hippocampus from sleep-deprived and Alzheimer’s disease mice - Yi Wei (Genetics and Molecular Biology, 2020)
Abstract We did a comparative analysis of the gene expression profiles of the hippocampus from sleep deprivation and Alzheimer’s disease (AD) mice. Differentially expressed genes (DEGs) were identified by comparing the transcriptome profiles of the hippocampus of sleep deprivation or AD mouse models to matched controls. The common DEGs between sleep deprivation and AD were identified by the overlapping analysis, followed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. The results showed that a total of 16 common DEGs showed similar change patterns in both sleep deprivation mice and AD mice. Sgk1, Ly6a, Atp6v0e, Hspb8, Htra1, Pdk4, Pfkfb3, Golm1, and Plin3 were up-regulated in the two disorders, whereas, Marcksl1, Fgd1, Scarb1, Mvd, Klhl13, Elovl2, and Vps29 were down-regulated. Acetyl-CoA metabolic process and lipid biosynthetic process were significantly enriched by those DEGs. The highly expressed DEGs and the two GO terms were associated with neuropathological changes according to the previous studies. As expected, sleep deprivation may contribute the AD development through these common DEGs.